Application of the Death Penalty in Narcotics Crime Cases: Human Rights and International Criminal Law Perspectives - Yudi Krismen; Zulkarnain S; Riadi Asra Rahmad; Herniwati; Arief Fahmi Lubis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The use of the death penalty in drug-related crimes remains a contentious issue globally, raising concerns about fundamental human rights and policies designed to curb drug trafficking. While some countries retain the death penalty as a tool to address drug offenses, citing its deterrent effect and its role in protecting public health, the human rights viewpoint strongly challenges such practices, focusing on the sanctity of the right to life. International legal frameworks set limits on the death penalty's application and urge states to refrain from actions deemed inhumane and ineffective. This article explores the implementation of the death penalty for drug crimes, considering both human rights perspectives and its relationship with international criminal law.